Venus Anadyomene: The Mythological Symbolism from Antiquity to the 19th Century - Newberry, Jenna Marie (My University, 2011)
This thesis includes reading the chosen artworks as a visual interpretation of the written mythological birth of Venus by the sea. Reading the selected painting as visual novels, the pictorial symbolism helps prove or disprove the true theme of the Venus. The writer bases her theory on the inclusion of mythological symbols that represent the Venus Anadyomene; scallop shell, dolphins, Aros, dove, sparrow, girdle, mirror, myrtle, and roses. The comparison of various artists' interpretations of this theme and the symbols they use to recognize the Venus as such is a substantial part of the research. The writer concludes in this thesis that the chosen art pieces are or are not a Venus Anadyomene, and in fact just a female nude entitled and themed fallaciously for an allure or ambiance. Through extensive research in the mythological symbolism of the Goddess of Love, the above-mentioned symbols used by various artists across several eras prove the Venus a true character of mythological history.
Thesis (M.A.)-University of Wisconsin, Superior, 2011. 30 leaves.
Keywords: Art History; Venus; symbols; Visual Arts; art; myth